Phospholipid Complex Technique for Superior Bioavailability of Phytoconstituents - Kattamanchi Gnananath; Kalakonda Sri Nataraj; Battu Ganga Rao (Tabriz University of Medical Sciences, 2017)
Phytoconstituents have been utilized as medicines for thousands of years, yet their application is limited owing to major hurdles like deficit lipid solubility, large molecular size and degradation in the gastric environment of gut. Recently, phospholipid-complex technique has unveiled in addressing these stumbling blocks either by enhancing the solubilizing capacity or its potentiating ability to pass through the biological membranes and it also protects the active herbal components from degradation. Hence, this phospholipid-complex-technique can enable researchers to deliver the phytoconstituents into systemic circulation by using certain conventional dosage forms like tablets and capsules. This review highlights the unique property of phospholipids in drug delivery, their role as adjuvant in health benefits, and their application in the herbal medicine systems to improve the bioavailability of active herbal components. Also we summarize the prerequisites for phytosomes preparation like the selection of type of phytoconstituents, solvents used, various methods employed in phytosomal preparation and its characterization. Further we discuss the key findings of recent research work conducted on phospholipid-based delivery systems which can enable new directions and advancements to the development of herbal dosage forms.